Medial knee pain in a collegiate wrestler - Donovan, L.; Grindstaff, T. L.; Carson, E. (Journal of Athletic Training, 2012)
Background: A 20 year-old male wrestler presented with mild left knee pain that started 2 hourspost-practice, while at the national tournament. Past medical history included a left grade II MCL sprain 8 months prior and a left medial meniscus repair 2 years prior. The athlete did not recall aspecific mechanism of injury, but described his knee being subjected to repetitive valgus forces during drills. There was no edema, ecchymosis, broken skin,or deformity of the knee. Mild tenderness (3/10) was noted over the MCL and medial joint line. Range of motion was within normal limits and pain free except for full passive knee flexion. All knee special tests were negative except the valgus stress test and McMurray`s test were positive for pain. Differential Diagnosis: MCL sprain, medial meniscus injury. Treatment: The athlete was referred to the on-site physician whodiagnosed the injury as a mild MCL sprain. The next day, he competed in two matches, which did not exacerbate his symptoms. Byday4 the pain increased to (5/10) and a small knee effusion developed. All vital signs were normal. The athlete was further examined by an on-site physician who diagnosed the injury as a medial meniscus tear. The athlete was placed in a knee brace and given crutches for ambulation. By the evening, the pain increased substantially (10/10), a large knee joint effusion developed, and erythema formed over the medial knee. The athlete was referred to an on-site physician, who aspirated his left knee and referred him to a localhospital emergency department. Based on the evolving presentation, the differential diagnosis changed to staphylococcus infection, cellulitis, gonococcal arthritis, or herpetic arthritis. While in the hospital vital signs remained normal, white blood cell count was reported normal, andthe synovial fluid was cultured. The athlete received IV morphine and Toradol to control the pain and was prescribed Percocet (2 tablets PRN every 4 hours) and indomethacin (25 mg tid). On day 5, the athlete traveled to hishome university and arrived early morning on Day 6. Upon arrival, he was taken to the emergency department, where his knee was re-aspirated andfluidcultured. All vital signs remained normal; however, the erythema had spread proximally. Based on clinical presentation, the attending orthopedic surgeon recommended arthroscopic debridement and irrigation. During the surgery,9 liters of normal saline was used to irrigate the joint, and hemovac was placed in the joint. After surgery, the athlete was placed on IV chephazolin. On day 8, the culture began to growstaphylococcus aureus bacteria, but the species was not yet identified. Therefore, the antibiotic was changed to Vancomycin. Two days later (day 10), the infection wasidentified as methicillin susceptible staphylococcus aureus (MSSA). On day 10, the athlete had a central catheter inserted (PICC line) in the right brachial vein that extended to the distal superior vena cava, which was used to administer chephazolin for 6 weeks.The athlete was discharged from the hospital on day 10. The athlete was able to return to fullparticipation after the PICC line was removed. Uniqueness: Most joint infections have a mechanism of whichbacteria enters through the joint capsule. In this case, there was no known disruption of the skin for bacteria to enter the joint and the original clinical examination presented as a mild MCL sprain. Conclusions: Infections may initially present as a musculoskeletal injury making it important for athletic trainers to serially monitor symptoms. In this case, the rapid increase in pain and effusion was atypical for a musculoskeletal injury.